Planning and Implementation of a Startup in a Modern Business Environment (Economics and region, 2019)
The purpose of the article is to identify and analyze the results of the implementation of successful start-ups and review the legislative aspects for their development and implementation; substantiation of possibilities for realization of a startup on launch of a food truck with the implementation of healthy food. The concept and types of startups are considered. It justifies the possibility of implementing a start-up to launch a food truck with a suggestion of healthy nutrition.
Keywords: start-up; food truck; healthy food; food market; entrepreneurship